Role of reinforcement methods in retention of composite restorations of primary anterior teeth - Ansari, Ghassem; Torabzadeh, Hassan; Malekafzali, Beheshteh; Yarmohammadi, Reza (Journal of Dental School, 2019)
Objectives This study aimed to evaluate the retention of composite restorations of primary anterior teeth reinforced with composite posts, glass fiber posts, para-pulpal pins with composite posts, and para-pulpal pins alone. Methods Forty freshly extracted sound primary canine teeth with at least two-third of the root length remaining were selected. After disinfection, the tooth crown was cut perpendicular to the longitudinal axis. Root canals were prepared and filled using zinc oxide eugenol paste. The teeth were randomly allocated into four groups and restored using one of the following: Composite posts, glass fiber posts, para- pulpal pins with composite posts, and para-pulpal pins alone. Composite cores were constructed while a preformed U-shaped orthodontic wire was placed in the composite tip, samples were then placed in a universal testing machine for measurement of retention. The minimum force required to dislodge the restoration or cause fracture was considered as the retentive strength. The collected data were analyzed using one-way ANOVA and Tukey’s test (P < 0.05). Results There were statistically significant differences between groups (P = 0.011). The mean retention in the para-pulpal pins with composite post group (131.72 ± 32.35N) was greater than that in composite posts (93.65 ± 24.45N), glass fiber post (95.92 ± 25.35N), and the para-pulpal pin group (95.34 ± 29.56N) (P < 0.05). Other differences were not significant (P > 0.05). Conclusion para-Pulpal pin alone may not help in improving the retention of full crown restoration of primary anterior teeth. However, when used along with a composite post, it appears to improve the retention of restoration.